Structural Analysis of Psycological Determinants in Driving Green Purchase Intention and Environmentally Conscious Behavior - Aisyah, Siti Nur; Nurrahmah, Mita (Universitas Medan Area, 2025)
This research investigates the relationships among Attitude Toward Behavior (ATB), Behavioral Intention (BI), Environmental Knowledge (EK), Purchase Intention (PI), and Perceived Consumer Effecti-veness (PCE) concerning Ecologically Conscious Consumer Behaviour (ECCB), focusing specifically on individuals aged 15–30 years. A quantitative research design was employed, using a convenience sam-pling method with 475 respondents. Data was collected via a structured survey and analyzed using SEM-PLS. The study assessed both direct and indirect effects to understand the mediating roles of BI and PI. The findings reveal that all tested direct and indirect paths are significant. ATB positively influences BI and PI. BI significantly affects ECCB and PI. EK shapes BI, ECCB, and PI. Finally, PI contributes to ECCB. Mediation analysis indicates that EK, PI, and BI serve as dominant mediators in both single and sequential mediation. This study strengthens the Theory of Planned Behavior (TPB) framework by empirically de-monstrating that positive ATB, EK, and PCE are crucial in shaping ethical consumption patterns among young people. The results highlight the pressing need to promote environmental awareness and empo-wer young consumers through focused educational initiatives and green marketing approaches that translate positive intentions into real sustainable practices.